A review of current construction guidelines to inform the design of rammed earth houses in seismically active zones. (15th August 2022) - Thompson, David; Augarde, Charles; Osorio, Juan Pablo
Abstract: Sustainability in the materials we use for construction is a prime concern, focusing on reducing the embodied energy and carbon footprints of the materials used. The cement used in concrete products is responsible for a significant proportion of Man's CO2 emissions and its production requires substantial energy input, as do fired clay products. For this reason, products formed from unfired earthen materials are of increasing interest and the current challenges include devising means of robust design for strength and to address durability concerns. One form of earthen construction that employs an in-situ method is rammed earth, and it is a technique experiencing a revival in various parts of the world. This revival has been partially supported by the development of guides and some standards although there is very little information as compared to traditional building materials. The objective of this paper is to provide a summary of the current guidelines found worldwide, specifically looking at rammed earth construction with seismic provisions and to propose a unified set of guidelines, demonstrated on a case study design. Highlights: Construction guidelines for rammed earth in seismic zones reviewed. Specifications for building details identified and differences highlighted. Unified specifications proposed to satisfy all guidelines. Sample seismic resistant house design provided.